Developments, bottlenecks, and opportunities in seed markets for improved forages in East Africa: The case of Kenya - Florez, Jesus Fernando; Karimi, Peggy; Paredes, John Jairo; Ángel, Natalia T.; Burkart, Stefan (Wiley, 2024)
Background Cattle farming plays a pivotal role in Africa's agricultural and livestock sector, poised for growth due to population expansion and rising per capita consumption of animal-sourced food. Forages are a primary source of feed for dairy cattle, significantly impacting production costs. While local forage varieties are preferred by dairy farmers, there has been an increase in the adoption of improved forages in recent years. However, the overall adoption rate is still low, for example, due to underdeveloped forage seed markets.